INFLUENCE OF ULTIMATE FRISBEE ON SOCIAL DEVELOPMENT FROM THE SPORTS FUNCTION PERSPECTIVE - Guan, Hongjing; Ma, Jiasheng (ASEAN Journal of Sport for Development and Peace, 2023)
Since the outbreak of the COVID-19 coronavirus epidemic, the impact on social development and the economy has been unprecedented. To prevent the COVID-19 epidemic, China has introduced a series of policies and measures, including home isolation and vaccine. However, working, studying, and living at home for a long time also bring unprecedented pressure on people's physical and mental health, which restricts people's work, communication, and participation in community activities. Public spaces like stadiums and gymnasiums have increasingly opened up due to the normalizing measures for epidemic prevention and control. People's thirst for sports and social activities has correspondingly grown. Ultimate Frisbee has become one of the most popular sports among young people because of its low participation threshold, sportswear fashion, engagement, and strong social content between men and women in their competition. In order to further support the rapid growth of Ultimate Frisbee in China, this study uses the techniques of literature review, questionnaire, interview, mathematical statistics, and logical analysis to examine the influences of Ultimate Frisbee on individual physical and mental health, interpersonal communication, economic development, and cultural development.